Screening and Following Up Harmful Alcohol Use “… is Not Necessarily Your Primary Focus”: A Qualitative Study Exploring Health Professionals’ Experiences Addressing Harmful Alcohol Use in a Norwegian Hospital - Tjelta T; Bogstrand ST; Lerdal A; Wüsthoff LEC; Edvardsen HME; Johannessen A (Journal of Multidisciplinary Healthcare, 2024)
Thomas Tjelta,1 Stig Tore Bogstrand,2– 4 Anners Lerdal,5,6 Linda Elise Couëssurel Wüsthoff,7,8 Hilde Marie Erøy Edvardsen,2 Aud Johannessen1,9 1Faculty of Health and Social Sciences, University of South-Eastern Norway, Porsgrunn, Norway; 2Section of Drug Abuse Research, Department of Forensic Science, Oslo University Hospital, Oslo, Norway; 3Faculty of Health Sciences, Department of Nursing and Health Promotion, Acute and Critical Illness, Oslo Metropolitan University, Oslo, Norway; 4Department of Public Health Science, Institute of Health and Society, Faculty of Medicine, University of Oslo, Oslo, Norway; 5Department of Interdisciplinary Health Sciences, Institute of Health and Society, Faculty of Medicine, University of Oslo, Oslo, Norway; 6Department of Research, Lovisenberg Diaconal Hospital, Oslo, Norway; 7Unit for Clinical Research on Addictions, Oslo University Hospital, Oslo, Norway; 8Norwegian Centre for Addiction Research, Institute of Clinical Medicine, University of Oslo, Oslo, Norway; 9The Norwegian National Centre for Ageing and Health, Vestfold Hospital Trust, Tønsberg, NorwayCorrespondence: Thomas Tjelta, Faculty of Health and Social Sciences, University of South-Eastern Norway, Kjølnes Ring 56, Porsgrunn, 3918, Norway, Tel +47 35 95 29 44, Email Thomas.Tjelta@usn.noIntroduction: Alcohol use remains a leading cause of excess mortality and morbidity worldwide, and identifying and following up harmful alcohol use represents a key component of alcohol harm reduction policies. This article explores health professionals’ experiences implementing these policies in a Norwegian hospital.Aim: To explore health professionals’ views and experiences of systematic screening and tailored follow-up of harmful and hazardous alcohol use in a Norwegian hospital.Methods: We conducted semi-structured interviews with 13 specialty registrars and nurses working in the emergency department and observation ward of a hospital in Oslo, Norway. Interviews were carried out between May and December 2022, coded using NVivo v.14 and analyzed thematically.Results: We identified three themes: (i) standardized and clinical assessment, referring to tensions between standardized and clinical alcohol risk assessment; (ii) formal and informal treatment guidelines, encompassing the informal patient care practices enacted in the emergency department and on the wards, and; (iii) training delivery and barriers to implementation, referring to the training penetration rate and identified need for “clear and simple” alcohol treatment guidelines.Conclusion: This study highlights tensions between alcohol-related harm and alcohol-related norms as these pertain to screening and following up harmful and hazardous alcohol use in a Norwegian hospital. Results suggest training should focus on zero alcohol recommendations, the use of assessment tools, the acceptability of screening to patients and “clear and simple” patient follow-up procedures.Keywords: alcohol, brief intervention, health policy, health promotion, screening